2017
DOI: 10.1155/2017/9129801
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Sex of Modern Greeks Based on the Foramen Magnum Region

Abstract: Sex determination is one of the principal aims when examining human skeletal remains. One method for sex determination is based on metric criteria using discriminant functions. However, discriminant function sexing formulas are population-specific. In the present study, we determined the use of the foramen magnum as well as the occipital condyles for sex determination on adults from a modern Greek population. Seven parameters were examined (4 obtained from the foramen magnum; 3 obtained from the occipital cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…The use of radiological methods such as X-ray, computed tomography (CT) and magnetic resonance imaging, is striking and provides data that is consistent with measurements derived through using calipers in estimation of dry skull diameters (Zheng et al, 2018). Previous morphometric cranial analyses using CT imaging measuring the accuracy rates have been conducted in different populations (Ekizoglu et al, 2016;Chovalopoulou & Bertsatos, 2017;RaghavendraBabu et al, 2012;Edwards et al, 2013;Abdel-Karim et al, 2015;Omer et al, 2015;Tellioglu et al, 2018;Vidisha et al, 2019).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The use of radiological methods such as X-ray, computed tomography (CT) and magnetic resonance imaging, is striking and provides data that is consistent with measurements derived through using calipers in estimation of dry skull diameters (Zheng et al, 2018). Previous morphometric cranial analyses using CT imaging measuring the accuracy rates have been conducted in different populations (Ekizoglu et al, 2016;Chovalopoulou & Bertsatos, 2017;RaghavendraBabu et al, 2012;Edwards et al, 2013;Abdel-Karim et al, 2015;Omer et al, 2015;Tellioglu et al, 2018;Vidisha et al, 2019).…”
Section: Introductionmentioning
confidence: 64%
“…The most reliable sexually dimorphic bones of the human skeleton are the innominate bones (Tambawala et al, 2016). From a forensic point of view, the basicranium has a resistant nature and is a commonly preserved part of human skeleton in disastrous injuries or due to the effects of inhumation and taphonomic processes compared to other craniofacial bones owing to its distinguishable location in the base of the skull, its thickness and the large volume of soft tissues covering it (Chovalopoulou & Bertsatos, 2017). One of the important landmarks of the basicranium is the Foramen Magnum (FM) that attracted considerable interest and has various scientific and legal applications especially in sexual dimorphism mainly in the context of having significantly large number of fragmentary remains such as victims of mass disasters or with decomposed skeletonized bodies (Toneva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In these two studies, the most significant gender differentiation in caudal appearance was in the foramen magnum. Sexual dimorphism of the foramen magnum was mentioned in a morphometric study in humans [38]. On the other hand, whether the foramen magnum shows sexual dimorphism in poultry may be the subject of further geometric morphometry and morphometric studies.…”
Section: Discussionmentioning
confidence: 98%
“…The use of univariate and multivariate functions by anthropologists has suggested that the sexual identity from the cranial samples can be accurately established from 65% to 88%. 13 , 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%